Electric and Magnetic Field Testing in Vicinity of 110/x kV Substations - Grbić, Maja; Pavlović, Aleksandar; Hrvić, Dejan; Vulević, Branislav (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
The levels of non-ionizing radiation (electric and magnetic fields) at power frequency, which occur near 110/x kV substations are analyzed in this paper. The results of electric field strength and magnetic flux density measurements in the vicinity of three typical substations of the aforementioned voltage level are shown. With the purpose of estimating the exposure of the population to these fields, the obtained results were compared to the reference maximum levels set for increased sensitivity areas, which amount to 2 kV/m for electric field and 40 μT for magnetic flux density. The objective of the conducted analysis is to reach general conclusions on the levels of electric and magnetic fields, which may occur in the vicinity of the substations mentioned above, and evaluate their compliance with the national regulations on the population protection from non-ionizing radiation